BLOCKCHAIN IMPLEMENTATION IN CONSTRUCTION: AN EMPIRICAL ANALYSIS OF THE BENEFITS IN NIGERIA - Akinrata Ebunoluwa Bimbola; Ayodeji Emmanuel Oke; Adegbembo Taiwo Fadeke (Journal of Surveying, Construction and Property, 2025)
Blockchain Technology (BcT) has emerged as a transformative force across various industries, including the construction sector. Stakeholders within the construction industry increasingly recognize its potential benefits in construction processes. This paper examines the benefits of BcT in Nigeria. The study utilized a survey design, in gathering information from questionnaires administered to construction professionals. Statistical tools such as Mean Item Scores (MIS) and Explanatory Factor Analysis (EFA) were used to analyze data from 222 respondents. A Cronbach’s α test was also used to verify the reliability of the instrument. The study found that the adoption and implementation of BcT in the construction industry are low and still in the initial stages. However, BcT should not be disregarded due to its promising outlook. The study also revealed that the top benefits of BcT for construction project performance in an emerging economy include achieving value for money, enhancing transparency in the construction process, intensifying collaboration among professionals, promoting homogeneity and effectiveness in project administration, accelerating infrastructure development, and improving the quality of services. BcT was treated as an autonomous technology in this paper. The paper highlights the need to study the current level of BcT implementation and its immense benefits in modern construction activities within an emerging market.